Pengaruh Kualitas Sumber Daya Manusia dan Profesionalisme Tehadap Prestasi Kerja melalui Komitmen Organisasi pada CV Oktaviana Tas Grosir Mojokerto - Winda Dwi Octavia; Siti Mujanah; Achmad Yanu Alif Fianto (Transformasi Manageria: Journal of Islamic Education Management, 2024)
In today's fierce business competition, it is important for a business industry to make various improvements in developing its business, especially in improving aspects of employee work performance to support the success of companies in the wholesale industry. This study aims to determine whether there is an effect of Human Resource Quality and Professionalism on Work Performance with Organizational Commitment as an Intervening Variable (Case Study at CV Oktaviana Bag Wholesale Mojokerto). This research method uses explanatory quantitative in explaining the effect of the independent variable with the dependent variable in this study. From the analysis conducted at CV Oktaviana Tas Grosir Mojokerto, the quality of human resources and professionalism has a significant effect on employee work performance with organizational commitment as an intervening variable that strengthens the relationship, while the reliability of measuring instruments is good but convergent validity still needs to be improved, with recommendations to improve employee training programs, a culture of professionalism, communication, and program evaluation.